Spatio-temporal evolution, climatic response and social impacts of locust breeding areas from 618 to 1949 in Cangzhou, Hebei, China - Feng, Chenxi; Li, Gang; Xu, Wei; Wang, Shuo; Wang, Xingxing; Gao, Xing (Frontiers in Earth Science, 2023)
Recent years have seen a significant increase in natural disasters and vicissitudes of the environment, making it imperative to investigate their spatio-temporal dynamics. Using records extracted from historical documents and focusing on a typical hazardous area—Cangzhou, this study reconstructed databases of locust plagues and related disasters from 618 to 1949 to analyze the spatio-temporal evolution of the locust plagues as well as the locust breeding areas under the influence of patterns of water environment, and to clarify the climatic system and the social response to the locust plagues. The results suggested that: (1) Locust plagues occurred chiefly from March to June, while frequency and grades of the locust plagues rose in volatility, with mainly slight or moderate locust plagues becoming severe or catastrophic, the impact of the locust plagues increasing significantly from the Ming Dynasty to the Republic of China and the 17th century was the peak. (2) Locust plagues were widespread throughout Cangzhou, frequently occurring in densely hydrographic networks with significant hydrophilia. The locust breeding areas were divided into four main types: the eastern sea coast locust breeding areas, the central river flood locust breeding areas, the northwestern lake shore locust breeding areas, and the southwestern internal plain flood locust breeding areas. (3) There was no significant correlation between the locust plagues and temperature, while precipitation was closely related to the locust plagues. Locust plagues were misaligned with river floods and synchronized with droughts. (4) Locust plagues were formed by a combination of climatic and social influences and act as a medium for transmitting negative impacts to social systems, resulting in social impacts and responses.